2020
DOI: 10.1186/s12931-019-1254-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diffusing lung capacity before and after neoadjuvant concurrent chemoradiation on postoperative pulmonary complications among patients with stage IIIA/N2 non-small-cell lung cancer

Abstract: Background and objective: This study aims to evaluate the impact of diffusing capacity of the lung for carbon monoxide (DLco) before and after neoadjuvant concurrent chemoradiotherapy (CCRT) on postoperative pulmonary complication (PPC) among stage IIIA/N2 non-small-cell lung cancer (NSCLC) patients. Methods:We retrospectively studied 324 patients with stage IIIA/N2 NSCLC between 2009 and 2016. Patients were classified into 4 groups according to DLco before and after neoadjuvant CCRT; normal-to-normal (NN), no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…Several studies have demonstrated that the incidence of PPC increases with severe impaired pulmonary function. [13][14][15][16][17]33,34 FEV1/FVC% reflects airway obstruction and airway resistance, hence significant decreases in this parameter indicate that patients have pulmonary ventilation dysfunction and the possibility of pulmonary complications after lung resection is increased. Fernandes et al reported that FEV1/FVC% < 60% is a predictor of postoperative mortality and PPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated that the incidence of PPC increases with severe impaired pulmonary function. [13][14][15][16][17]33,34 FEV1/FVC% reflects airway obstruction and airway resistance, hence significant decreases in this parameter indicate that patients have pulmonary ventilation dysfunction and the possibility of pulmonary complications after lung resection is increased. Fernandes et al reported that FEV1/FVC% < 60% is a predictor of postoperative mortality and PPC.…”
Section: Discussionmentioning
confidence: 99%
“…12 The rate of PPC is established as related to impaired pulmonary function. [13][14][15][16][17] Alam et al reported significant differences in the percentages of predicted forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV1) in patients who developed atelectasis and respiratory tract infection following cardiac surgery. 14 Shin et al found that diffusing capacity of the lung for carbon monoxide (DLco) value before neoadjuvant concurrent chemoradiotherapy was significantly associated with risk of PPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A capacidade de difusão do pulmão para monóxido de carbono será realizada usando o sistema Vmax 22 (Sensor Medics, Yorba Linda, CA, EUA), de acordo com os critérios da American Thoracic Society / European Respiratory Society. 28 DLCO consiste em uma mistura de gases que é monóxido de carbono (0,3 %), acetileno (0,3%), metano (0,3%), oxigênio (21%), nitrogênio. 29…”
Section: Questionário De Incapacidade De Oswestry Modificado (Modq)unclassified
“…[10][11][12] However, only a few studies have investigated the incidence and risk factors for PPCs after neoadjuvant concurrent CRTx for NSCLC. 13,14 Moreover, predictive or discriminative factors, including neoadjuvant CRTx following surgery, for assigning patients with advanced NSCLC to multimodality treatment are still not established. Therefore, this study aimed to investigate the incidence and risk factors of PPCs after neoadjuvant concurrent CRTx and to construct a nomogram to help identify the subset of patients at an increased risk of PPCs.…”
Section: Introductionmentioning
confidence: 99%